MENATA AGROWISATA “KAMPUNG WISATA GULA AREN” DESA BELIMBING KECAMATAN PUPUAN TABANAN DI MASA PANDEMI - Soniari, Ni Nengah; Adhika, I Made; Suniti, Ni Wayan; Siti, Ni Wayan; Astariyani, Ni Luh Gede (Buletin Udayana Mengabdi, 2021)
Belimbing Village is a village in Pupuan District, Tabanan Regency, which is rich in natural tourism potential and community traditions but has not been managed optimally. To spur the development of tourism in this village, the village government and the Tabanan Regional Government are developing tours with the brand “Palm Sugar Park”. This thematic is taken from the village's superior product in the form of palm sugar and its processing tradition which is very interesting as a special interest tourist attraction. Tourists who are interested in learning how to make preparations from palm sap can visit Belimbing village while enjoying the natural beauty of the unspoiled countryside. The team from the Partner Village Development Program (PPDM) has gradually arranged the locations and attractions spots and prepared other supporting facilities to welcome tourists in the New Normal era. The stages of activities carried out are assistance to palm sugar farmer groups in increasing the quality and quantity of their production; determine the attraction spots of palm sugar processing; educate pokdarwis and palm sugar farmer groups and other communities to implement health protocols during the pandemic and provide assistance in making PERDES regarding agro-tourism in Belimbing village. The end goal is that society is economically empowered and continues to exist in the face of changing conditions of the new life order.Abstrak juga ditulis dalam bahasa Inggris.